Prognostic value of red blood cell distribution width-to-albumin ratio in patients with Cardiogenic shock - A cohort study - Yangjing Xue; Fangning Rong; Lei Li; Kangting Ji (Heliyon, 2025)
Objective: This study was found to demonstrate whether red blood cell distribution width -to-albumin ratio (RA) can effectively evaluate the prognosis of Cardiogenic shock (CS) patients and to explore the relationship between RA vs. inflammation and water retention. Methods: This cohort study included only adults (age≥18) with CS. Data were obtained from the Medical Information Mart for Intensive Care III (MIMIC-III) database and the Second Affiliated Hospital and Yuying Children's Hospital of Wenzhou Medical University (2016–2021). Cox proportional hazard regression was used to assess the relationship between RA and all-cause mortality. Logistic regression was used to assess the relationship between RA and sepsis occurrence and renal replacement therapy (RRT). Receiver operator characteristic (ROC) curve analysis and general linear correlation analysis were used to assess the deeper relationship between RA and CS. Results: A total of 720 CS patients were included. Cox proportional hazard regression showed that the HR (95 % CIs) for all-cause mortality in 30-day in the higher RA groups (4.79–5.84 ml/g and >5.84 ml/g) in quartile was 1.99 (1.32, 2.98) and 2.04 (1.36, 3.06), respectively, in the unadjusted model. The same correlation existed in model 2 and model 3 after further adjustment of possible covariates. Similar relationships were also observed for 90-day and one-year all-cause mortality. ROC curve analysis indicated that the predictive ability of RA on mortality risk of CS patients was similar to that of sequential organ failure assessment score (SOFA) and simplified acute physiology score II (SAPS II) (P > 0.05). The area under the curve (AUC) of RA, SOFA, and SAPS II were not statistically different (0.612, 0.615, and 0.656, respectively). Logistic regression showed that RA and renal replacement therapy occurred, and the prevalence of Sepsis was closely related. General linear correlation analysis indicated a linear correlation between RA and C-reactive protein, brain natriuretic peptide. Conclusion: The results shown that RA is an independent risk factor for CS patients. Besides, the predictive ability of RA on mortality risk of CS patients was similar to SOFA and SAPS II scores. This prediction ability may be related to inflammation and water retention.